A Randomized Placebo-Controlled Trial of Combination Therapy With Post-triple-antibiotic-therapy Fecal Microbiota Transplantation and Alginate for Ulcerative Colitis: Protocol - Ishikawa, Dai; Zhang, Xiaochen; Nomura, Kei; Seki, Natsumi; Haraikawa, Mayuko; Haga, Keiichi; Shibuya, Tomoyoshi; Kim, Yun-Gi; Nagahara, Akihito (Frontiers in Medicine, 2022)
Background: Fecal microbiota transplantation (FMT) has been widely performed for ulcerative colitis (UC) treatment at the clinical trial stage. Previous reports have used multiple FMT methods to enhance the colonization of healthy donor microbiota in the recipient’s intestines. FMT following triple antibiotic therapy with amoxicillin, fosfomycin, and metronidazole (A-FMT) is not only effective but also requires only one FMT, which improves dysbiosis caused by reduced Bacteroidetes diversity in patients with UC. Alginate and its derivatives have the potential to induce the growth of intestinal bacteria including Bacteroides members and produce short-chain fatty acids (SCFAs), which are beneficial in regulating overactive autoimmunity. Our trial aims to investigate whether post-intervention with alginate, which can improve the intestinal environment, will enhance the therapeutic effect of A-FMT in UC and increase the long-term remission rate. Methods and analysis: This trial is a double-blinded, randomized, placebo-controlled, parallel assignment trial. Patients with UC and fecal donation candidates will undergo strict screening before being involved in the trial. Eligible patients are randomly divided into two groups: one group will drink one bottle of alginate twice a day for 8 consecutive weeks after A-FMT, while the other group will take a placebo instead of the alginate drink. The primary endpoints are the changes in the Total Mayo Score at 8 weeks after study initiation and A-FMT from baseline. The secondary endpoint is the comparison of clinical features, microbiota, and metabolomic analysis before and after 8 weeks of study food intake. Changes at 6, 12, 18, and 24 months after A-FMT will be assessed. Finally, a subpopulation analysis of the relationship between patients and donors is an exploratory endpoint. Discussion: The FMT post-treatment used in this study is an oral alginate drink that is easily accepted by patients. If the regimen achieves the desired results, it can further improve the A-FMT regimen and provide evidence for clinical practice guidelines for UC.